Analysis of MicroRNA Profile Alterations in Extracellular Vesicles From Mesenchymal Stromal Cells Overexpressing Stem Cell Factor - Zubkova, Ekaterina; Evtushenko, Evgeniy; Beloglazova, Irina; Osmak, German; Koshkin, Phillip; Moschenko, Alexander; Menshikov, Mikhail; Parfyonova, Yelena (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem/stromal cells (MSCs) represent a promising tool to treat cardiovascular diseases. One mode of action through which MSCs exert their protective effects is secretion of extracellular vesicles (EVs). Recently, we demonstrated that rat adipose-derived MSC-overexpressing stem cell factor (SCF) can induce endogenous regenerative processes and improve cardiac function. In the present work, we isolated EVs from intact, GFP- or SCF-overexpressing rat MSC and analyzed microarray datasets of their miRNA cargo. We uncovered a total of 95 differentially expressed miRNAs. We did not observe significant differences between EVs from GFP-MSC and SCF-MSC that may indicate intrinsic changes in MSC after viral transduction. About 80 miRNAs were downregulated in EVs from both SCF- or GFP-MSC. We assembled the miRNA-based network and found several nodes of target genes among which Vim Sept3 and Vsnl1 are involved in regulation of cellular migration that is consistent with our previous EVs data. Topological analyses of the network also revealed that among the downregulated miRNA-rno-miRNA-128-3p that regulates plenty of targets is presumably associated with chemokine signaling pathways. Overall, our data suggest that genetic modification of MSC has a great impact on their miRNA composition and provide novel insights into the regulatory networks underlying EV effects.